Effect of Pseudomonas fluorescens Bacteria on Sow and Pocket Fertilization Methods in Ultisol Soil Planting Media on Phaseolus radiatus L. Plant Growth - Erwin Junaidi Lubis; Hariyanto (Athallah Publishing globalindo, 2026)
Pseudomonas fluorescens is one type of Pseudomonas bacteria that is good for plants. This bacterium is included in a group of bacteria that promote plant growth (PGPR). Pseudomonas fluorescens can play an active role in plants, which can increase plant resistance to disease, this is because it can produce an antibiotic called phenazine and an aerobic, gram negative, and ubiquitous organism found in agricultural soils and can adapt well to grow and develop in the Rhizosphere. Ultisol soil is a type of soil where the level of soil fertility is low, so it is very rarely used, one of the elements of phosphorus (P) becomes inward for Phaseolus radiatus L. plants so that inorganic fertilization methods are needed in spurring its growth. This study aims to determine the ability of Pseudomonas fluorescens bacteria as phosphate solvents in Phaseolus radiatus L. plants and effective fertilization methods for plant growth. The results showed that the ability of Pseudomonas fluorescens bacteria could make the growth of Phaseolus radiatus L. become better and more fertile and had a real effect on the dose given high in all research parameters.